Endoscopic Endonasal Transplanum Approach to the Paraclinoid Internal Carotid Artery - Lai, Leon T.; Morgan, Michael K.; Snidvongs, Kornkiat; Chin, David C. W.; Sacks, Ray; Harvey, Richard J. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To investigate the relevance of an endoscopic transnasal approach to the surgical treatment of paraophthalmic aneurysms.Setting Binasal endoscopic transplanum surgery was performed.Participants Seven cadaver heads were studied.Main Outcome Measures (1) Dimensions of the endonasal corridor, including the operative field depth, lateral limits, and the transplanum craniotomy. (2) The degree of vascular exposure. (3) Surgical maneuverability and access for clip placements.Results The mean operative depth was 90 ± 4 mm. The lateral corridors were limited proximally by the alar rim openings (29 ± 4 mm) and distally by the distance between the opticocarotid recesses (19 ± 2 mm). The mean posteroanterior distance and width of the transplanum craniotomy were 19 ± 2 mm and 17 ± 3 mm, respectively. Vascular exposure was achieved in 100% of cases for the clinoidal internal carotid artery (ICA), ophthalmic artery, superior hypophyseal artery, and the proximal ophthalmic ICA. Surgical access and clip placement was achieved in 97.6% of cases for vessels located anterior to the pituitary stalk (odds ratio [OR] 73.8; 95% confidence interval [CI] 7.66 to 710.8; p = 0.00).Conclusion The endoscopic transnasal approach provides excellent visualization of the paraclinoid region vasculature and offers potential surgical alternative for paraclinoid aneurysms.
Keywords: endoscopic endonasal approach; ophthalmic artery aneurysm; superior hypophyseal artery aneurysm; paraclinoid aneurysm; paraophthalmic aneurysm